Anti-HLA Class I alloantibodies in platelet transfusion refractoriness: From mechanisms and determinants to therapeutic prospects - Adèle Couvidou; Adèle Couvidou; Adèle Couvidou; Adèle Couvidou; Gabriel Rojas-Jiménez; Gabriel Rojas-Jiménez; Gabriel Rojas-Jiménez; Gabriel Rojas-Jiménez; Arnaud Dupuis; Arnaud Dupuis; Arnaud Dupuis; Arnaud Dupuis; et al. (Frontiers in Immunology, 2023)
Patients with hematological disorders and severe thrombocytopenia require extensive and iterative platelet transfusion support. In these patients, platelet transfusion refractoriness represents a serious adverse transfusion event with major outcomes for patient care. Recipient alloantibodies against the donor HLA Class I antigens expressed at the cell surface of platelets result in a rapid removal of transfused platelets from the circulation and thus, therapeutic and prophylactic transfusion failure leading to a major bleeding risk. In this case, the only way to support the patient relies on the selection of HLA Class I compatible platelets, an approach restricted by the limited number of HLA-typed donors available and the difficulty of meeting the demand in an emergency. However, not all patients with anti-HLA Class I antibodies develop refractoriness to platelet transfusions, raising the question of the intrinsic characteristics of the antibodies and the immune-mediated mechanisms of platelet clearance associated with a refractory state. In this review, we examine the current challenges in platelet transfusion refractoriness and detail the key features of the antibodies involved that should be considered. Finally, we also provide an overview of future therapeutic strategies.